The Impact of Undernutrition on Cognition in Children with Severe Malaria and Community Children: A Prospective 2-Year Cohort Study. (10th November 2021) - Mburu, Waruiru; Conroy, Andrea L; Cusick, Sarah E; Bangirana, Paul; Bond, Caitlin; Zhao, Yi; Opoka, Robert O; John, Chandy C
Abstract: Background: The frequency of recovery from undernutrition after an episode of severe malaria, and the relationship between undernutrition during severe malaria and clinical and cognitive outcomes are not well characterized. Methods: We evaluated undernutrition and cognition in children in Kampala, Uganda 18 months to 5 years of age with cerebral malaria (CM), severe malarial anemia (SMA) or community children (CC). The Mullen Scales of Early Learning was used to measure cognition. Undernutrition, defined as 2 SDs below median for weight-for-age (underweight), height-for-age (stunting) or weight-for-height (wasting), was compared with mortality, hospital readmission and cognition over 24-month follow-up. Results: At enrollment, wasting was more common in CM (16.7%) or SMA (15.9%) than CC (4.7%) (both p < 0.0001), and being underweight was more common in SMA (27.0%) than CC (12.8%; p = 0.001), while prevalence of stunting was similar in all three groups. By 6-month follow-up, prevalence of wasting or being underweight did not differ significantly between children with severe malaria and CC. Undernutrition at enrollment was not associated with mortality or hospital readmission, but children who were underweight or stunted at baseline had lower cognitive z-scores than those who were not {underweight, mean difference [95% confidence interval (CI)] −0.98 (−1.66, −0.31), −0.72 (−1.16, −0.27) and −0.61 (−1.08, −0.13); and stunted, −0.70 (−1.25, −0.15), −0.73 (−1.16, −0.31) and −0.61 (−0.96, −0.27), for CM, SMA and CC, respectively}. Conclusion: In children with severe malaria, wasting and being underweight return to population levels after treatment. However, being stunted or underweight at enrollment was associated with worse long-term cognition in both CC and children with severe malaria.